Antibiotic resistance, virulence factors and genotyping of Pseudomonas aeruginosa in public hospitals of northeastern Mexico - González-Olvera, Eliab M; Pérez-Morales, Rebeca; González Zamora, Alberto; Castro-Escarpulli, Graciela; Palma-Martínez, Ingrid; Alba-Romero, José J (The Journal of Infection in Developing Countries, 2019)
Introduction: Pseudomonas aeruginosa is the second most prevalent opportunistic pathogen causing nosocomial infections in Mexico. This study evaluated antibiotic resistance, production of virulence factors and clonal diversity of P. aeruginosa strains isolated from patients undergoing nosocomial infections in public hospitals of northeastern Mexico. Methodology: Ninety-two P. aeruginosa isolates from urine culture, Foley catheter, ear, wounds, respiratory tract secretions, scalp, blood culture, bronchoalveolar lavage, expectoration and cerebrospinal fluid causing nosocomial infections were analyzed. The isolates were identified by MALDI-TOF and antibiotic resistance profiles obtained by MicroScan®. The production of virulence factors was analyzed with spectrophotometric techniques and isolates genotyped by ERIC-PCR. Results: Out of the 92 isolates, 26 (28.2%) were found to be multidrug resistant (MDR); 21 (22.7%) were classified as extremely drug resistant (XDR). Highest resistance rate was found for gatifloxacin (42%) while ciprofloxacin accounted for the antibiotic with the lowest resistance rate (2%). Bronchoalveolar lavage isolates produced the highest amounts of virulence factors: biofilm (44.4% ± 2.7%), elastase (58.5% ± 4.3%), alkaline protease (60.1% ± 5.0%); except for pyocyanin production. The ERIC-PCR assay showed 83 genetic patterns (90% clonal diversity) and 13 isolates had 100% genetic similarity, forming 4 real clones, 3 of these clones were obtained from different anatomical site and/or hospital. Conclusions: Antibiotic resistance and virulence factors production was heterogeneous among samples analyzed. Genotyping of P. aeruginosa strains showed high genetic diversity in the studied isolates.